ANATOMICAL, PHARMACEUTICAL AND CLINICAL TERMINOLOGY IN LATIN CLASSES (Journal of Universal Science Research, 2024)
The article “Anatomical, pharmaceutical and clinical terminology in Latin classes” talks about the interdisciplinary branch of knowledge - terminology. Three leading terminological subsystems are examined in more detail: anatomical-histological terminology, pharmaceutical terminology and clinical terminology. The article discusses the principles of the model for compiling Latin terms and their Greek doublets (TE) in the names of functional disorders, in the names of pathological processes and conditions, in pharmaceutical terminology and recipe